Assessing the Role of Digital Literacy in Investment Decisions among Graduate Business Students in Nepal: The Mediating Effects of Peer Group Influence - Subedi, Dhurba Prasad; Bhandari, Dilli Ram (Multi-Disciplinary Explorations: The Kasthamandap College Journal, 2024)
In the evolving landscape of global finance, digital literacy has emerged as a critical determinant of investment decision-making among graduate business students in Nepal. This research explores the intricate interplay between digital literacy and investment decisions, focusing specifically on how peer group influence mediates this relationship. To achieve the stated objective, data were collected from the primary source using a structured questionnaire administered through purposive sampling technique. The respondents comprised 175 business graduate students studying inside the Kathmandu valley who invest in Nepalese market using digital platform. The SmartPLS 4.0 was used to analyze the structural relationships within the proposed theoretical model. The findings of this study validated the set hypotheses that digital literacy significantly impacts investment decisions, that students who are more digitally literate are better equipped to make informed investment choices. Moreover, the study reveals that peer group influence plays a crucial mediating role in the relationship between digital literacy and investment decisions. Findings from this study aim to contribute to the literature on financial literacy and behavioral finance by providing insights into the mechanisms through which digital literacy and social influences shape investment choices.